The Approach to the Library Institution in 2015-2018 Information Society Strategy and Action Plan of Turkey - Şenol Karadeniz; Bülent Yılmaz (Türk Kütüphaneciliği)
Starting from the assumption that there is an organic link between the information policies and the library institution, the approach towards library institution as a part of information society in Information Society Strategy and Action Plan of 2015-2018 prepared by the Turkish Ministry of Development is discussed in this study. Covering the time period between 2015 and 2018 Information Society Strategy and Action Plan consists of 72 actions in 8 main topics. 26 institutions have been held responsible for the actions, and it has been stated that these actions are going to be monitored by 30 indicators. In this study, it has been examined how frequently the library is used as a term in the content of Information Society Strategy and Action Plan. Afterwards, it is aimed to determine the points where all strategies, aims and action plans in Information Society Strategy and Action Plan might be in relation with the library institution. Lastly, the strategy document is examined in terms of the field of Information and Documentation Management. Consequently, the library was used directly as a term only in 2 main topics out of 8. Apart from these, however, it is understood that issues such as the dissemination of cloud services; the infrastructure measures to reduce the digital division; the training of qualified human resources needed in the ICT sector and the penetration of information technology in society are also in relation with the libraries. In the strategy document it is understood that the library institution is not seen as an organic element supporting national information policies. Some suggestions have been presented on the basis of the results obtained through this study.